Comparison of step-by-step kinematics of normal and assisted 60 m sprints with different loads in experienced sprinters - van den Tillaar, R. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to compare step-by-step kinematics of normal and assisted 60 m sprints with different loads in experienced sprinters. Step-by-step kinematics were measured using inertial measurement units integrated with a 3-axis gyroscope and a laser gun in eleven participants during a normal 60 m sprint and sprints with a 3, 4, or 5kg pulling force. The main findings were that using increased assisted loads resulted in faster 60 m times, which was a result of a higher step velocity caused mainly by longer step lengths. In terms of practical application, it is notable that employing this approach, when using a 5 kg assisted load can help athletes reach higher step velocities and maintain these velocities longer, which could be a training impulse to move the speed barrier upwards.